Analysis of Teacher’s Competence About Mathematics Materials for National Final Examination - Syafriandi Syafriandi; Dina Fitria (Pelita Eksakta, 2018)
Principal component in teaching mathematics for teacher is professional competence. It cover how the teacher understand the material of subject matter itself. Teaching Mathematics in Junior High School, teacher have to understand completely in Numbers, Algebra, Geometry and measurements, and also Statistics and probability. Based on the exam and discussion in workshop, known that math teacher in Pesisir Selatan having problems in teaching Geometry and measurement and also Statistics and probability. The problems are complexity of teaching materials, error in translating competence standard and basic competence into lesson plan, time management and student’s motivation in studying math. Solution that offered to the teacher are translating basic competence into learning process and trick how to teach Geometry and Statistics especially. Teaching geometry by explain all geometry object, i.e. plane and space simultaneously and compare each object directly. Teaching statistics and probability starting by counting process.